INOVASI FINTECH DAN IMPLIKASINYA TERHADAP PERBANKAN KONVENSIONAL DI ERA MASYARAKAT DIGITAL - Dicky Arpillo Siregar; Taufik Hidayat; Fatimah Pohan; Ruhilah Lubis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The aim of this research is to analyze the impact of Financial Technology (FinTech) innovation on conventional banking and identify the challenges and opportunities that arise in the era of digital society. This research also aims to explore how conventional banks can adapt to technological developments and competition from FinTech companies. The research method used is a qualitative method with a case study approach. Data was collected through in-depth interviews with professionals in the financial industry, document analysis, and a review of relevant literature. Data analysis was carried out thematically to identify patterns and relationships between the variables studied. The research results show that FinTech innovation brings various benefits to consumers, such as ease of access, speed of service, and lower costs. However, conventional banks face significant challenges in adapting to new technology and the more flexible business models of FinTech companies. Conventional banks that successfully adapt are those that are able to integrate digital technology into their operations, collaborate with FinTech companies, and offer more personalized and innovative services. This research also finds that regulations that are adaptive and support innovation are very important to create a balanced financial ecosystem. Conventional banks need to develop comprehensive digital strategies to remain relevant and competitive in this digital era. With the right strategy, conventional banks can increase operational efficiency, expand service coverage and improve customer experience. This research provides valuable insights for conventional banks, FinTech companies and regulators in managing the dynamics of the financial industry in the digital era, as well as encouraging the creation of an innovative and inclusive financial ecosystem.